Water Disclosure in Indonesian Agriculture: The Roles of Ownership and Political Connections - Wulandari, Asya Aulia; M, Poppy Nurmayanti (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
This study examines the impact of ownership structures, in conjunction with political connections, on corporate water disclosure practices in Indonesian agriculture firms listed on the Indonesian Stock Exchange (IDX) from 2019 to 2023. The sample used in this study derive from Indonesian agricultural firms listed on the Indonesian Stock Exchange (IDX), a purposive sampling method was applied to all of the 16 suitable firms for the study, and panel data multiple regression analysis was conducted to test the proposed hypotheses. The analysis reveals that institutional ownership, managerial ownership, public ownership, and political connections have a significant influence on corporate water disclosure. Additionally, this study employs additional measurements by including control variables namely, firm size, leverage, return on asset and sales growth.